Development of response - dilution maps for super duplex stainless steel claddings deposited by FCAW. (2016) - Senthilkumar, B.; Kannan, T.; Arun, K.K.
This paper aimed at developing the response - dilution maps using response surface methodology. The proposed map is vital to achieve desired composition, properties and weld bead dimensions in stainless steel claddings. Controlled heat input and percentage dilution will enable the matching of surfaced layer properties with intended alloy. The flux cored arc welding (FCAW) process was selected because of its smooth bead appearance, deposition rate, automation and positional capabilities. The relationship between the welding parameters and responses were expressed as mathematical models. The identified input parameters are welding voltage, wire feed rate, welding speed, nozzle to plate distance and welding gun angle. The models were validated statistically and experimentally. The proposed map explores the effect of interaction between the welding voltage and wire feed rate on the bead geometry and percentage dilution. The effect of interaction between welding voltage, wire feed rate and nozzle to plate distance on the responses reinforcement height, bead width and percentage dilution was studied using response dilution maps.